Light activated pulsatile drug delivery for prolonged peripheral nerve block. (April 2022) - Prieto, Martin; Usón, Laura; Garcia-Salinas, Sara; Yus, Cristina; Landa, Guillermo; Alejo, Teresa; Lujan, Lluis; Perez, Marta; Irusta, Silvia; Sebastian, Victor; Mendoza, Gracia; Arruebo, Manuel
Abstract: Regional anesthesia is widely used in peripheral nerve block and in neuraxial anesthesia to reduce anesthetics systemic side effects and shorten recovery times. However, when applied as a single injection (e.g., peripheral nerve block) it is limited by the duration of its effect. Herein, we develop a thermoresponsive nanogel based on poly(oligoethylene glycol methacrylate) containing the long-lasting anesthetic bupivacaine, which can be externally activated by using near-infrared light due to the photothermal properties of hollow gold nanoparticles embedded in the nanogel which facilitate its phase transition, triggering drug release at a controlled temperature above body temperature. Bupivacaine in vitro release can be repeatedly triggered to achieve a controlled pulsatile release of the drug due to the reversible nature of the thermosensitive nanogel, achieving a spatio-temporal control of the release. In vivo sciatic nerve block demonstrates that whereas the administered dose of free bupivacaine produces sensory block and impaired motor function for 2 h, the equivalent bupivacaine dose included in the developed release system can significantly prolong its neurobehavioral anesthetic effect for over 6 h. This release system can also be reactivated multiple times by subsequent irradiation cycles without observing detrimental toxicity in the infiltrated tissues.